EVALUATION OF AC-BC MIXTURES STABILITY AND FLOW VALUES ON THE USE OF ANALOG AND DIGITAL MARSHALL TEST EQUIPMENT: Evaluasi Nilai Stabilitas dan Flow Campuran AC-BC Pada Penggunaan Alat Uji Marshall Analog dan Digital - Sulistyono, Sonya; Badriani, Ririn Endah; Zakaria, Zakaria (Jurnal Rekayasa Sipil dan Lingkungan, 2017)
Marshall test-equipment is used to determine the stability of the flow and MQ of AC-BC pavement. It can be an analog and a digital test-equipment. Analog test-equipment reading the data manually dependens on the operator skills. While the digital test equipment uses a computer system produces maximum data with minimum operator. The research is conducted based on a mixture SNI 06-2489-1991 AC-BC with five variation of asphalt content. The presumptions of the test result of Marshall characteristic are found out as: the direct observation-analogue gets the stability (kg) = 1490.49; Flow (mm) = 4.48; MQ (kg / mm) = 335.55. The visualization analogue gets the stability (kg) = 1482.91; Flow (mm) = 4.44; MQ (kg / mm) = 336.48. The digital test-equipment gets the stability (kg) 1508.36; Flow (mm) = 4.42; MQ (kg / mm) = 342.93. Based on the three different analysis evenly show that there are no different significantly from the test result by using the direct observation-analogue, the visualization analogue, and the digital Marshall test-equipment. Alat uji Marshall digunakan untuk mengetahui stabilitas terhadap kelelehan plastis (flow) dan MQ dari lapis perkerasan AC-BC. Tipe alat pengujian Marshall dapat berupa analog dan digital. Alat uji analog dengan pembacaan data manual sangat bergantung pada ketrampilan operator. Alat uji digital menggunakan sistem komputer, sehingga menghasilkan data maksimum dengan operator minimum. Penelitian dilaksanakan berdasarkan SNI 06-2489-1991 pada campuran AC-BC dengan lima variasi kadar aspal. Hasil pengujian didapatkan nilai rata-rata alat uji analog pengamatan langsung: stabilitas (kg) = 1490,49; Flow (mm) = 4,48; MQ (kg/mm) = 335,55. Alat uji analog pengamatan perekaman video: stabilitas (kg) = 1482,91; Flow (mm) = 4,44; MQ (kg/mm) = 336,48. untuk alat uji digital menghasilkan stabilitas (kg) = 1508,36; Flow (mm) = 4,42; MQ (kg/mm) = 342,93. Berdasarkan analisa perbedaan tiga rata-rata menunjukkan tidak terdapat perbedaan signifikan hasil pengujian menggunakan alat uji Marshall analog pengamatan langsung, perekaman video dan digital.